Pemaknaan Kalimat Lâ Ilâh Illâ Allâh Menurut Said Nursi - Ahsanul Anam (Department of Aqidah and Islamic Philosophy, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2013)
This article explores the ideas of Said Nursi meaning of the phrase “Lâ ilâh illa Allâh”. The article concludes that God is perfect and He is there without a cause, because if there is a reason for him that means the dependency does not make perfect. God was the first manifestation of the most sublime. Therefore, God is the substance most original and ever-present. His essence itself be a sufficient cause for the manifestation of His eternity. For Said Nursi, the human mind may not be able to understand God directly. Therefore, there needs to be an explanation of God’s creation. Nursi interpret the phrase la ilaha illallah which makes everything that exists in this universe like a meaningful pieces that reflect the unity of God as Rabb al-‘Âlamîn. By knowing his creation, it will be easy to know God.